On Convergence of Iterative Procedures for Analysis of Complex Linear Dynamics Systems by Means of Partial Models - T.L. Stańczyk (Engineering Transactions, 1992)
Problems of iterative convergence in the analysis of complex dynamic systems with the use of partial models are dealt with. Linear systems are considered. Conditions and ranges of convergence are determined for two basic iteration procedures: the so-called weak and the strong associations of masses in the complete model. Damping in the system is found to accelerate convergence of the procedures.